Profil Sekolah Menengah Pertama Negeri Se- Kecamatan Sangir Jujuan Ditinjau Berdasarkan Standar Prasarana - Susi Indra Fitri; Syahril Syahril; Ermita Ermita; Irsyad Irsyad (Universitas Negeri Padang, 2021)
This research was based on the problems that researchers encountered in the UPT SMPN (06, 17, 28, 30) South Solok related infrastructure that was not in accordance with the infrastructure standards stipulated in the Regulation of the Minister of National Education number 24 of 2007. This is to describe the suitability of existing infrastructure in schools with infrastructure standards. This type of research is descriptive with qualitative methods, research data collection using interview techniques, observation, documentation, which is the source of the data in this study is the principal and vice principal in the field of school inventory. The results showed that (1) the classrooms of the UPT SMPN (06,17,28,30) Solsel were very in accordance with the infrastructure standards and even exceeded in terms of the number that had been set, (2) the library room of UPT SMPN (06,17,28,30) very in accordance with infrastructure standards, (3) the IPA laboratory room of UPT SMPN 06 is very suitable, UPT SMPN 17, 28 is suitable, and UPT SMPN 30 is not suitable, (4) the leadership room of UPT SMPN (06,17,28,30) is very suitable , (5) the UPT SMPN teacher room (06.30) is very suitable, the UPT SMPN (17.28) is not suitable, (6) the UPT SMPN administration room (06,17,28) is very suitable, the UPT SMPN 30 is not suitable, (7) the place of worship UPT SMPN (06,17,28) is very suitable, UPT SMPN 30 is not suitable, (8) UPT SMPN 28 counseling room is very suitable, UPT SMPN 06 is suitable, and UPT SMPN (17,30) is not suitable, (9) the UPT SMPN 28 UKS room is very suitable, the UPT SMPN (06,17,30) is not suitable, (10) the student organization UPT SMPN 28 is very suitable, the UPT SMPN (06,17,30) is not suitable, (11) latrines UPT SMPN (06,17,28) is very suitable, UPT SMPN 30 Turtle appropriate, (12) warehouse UPT SMPN 17 is very suitable, UPT SMPN (06,28) is not suitable, and UPT SMPN 30 is not suitable, (13) UPT SMPN 28 circulation space is suitable, UPT SMPN (06,17,30) is not appropriate, (14) the place to play / exercise UPT SMPN (06,17,28) is appropriate, UPT SMPN 30 is not in accordance with the infrastructure standards in Permendiknas number 24 of 2007.